2017
DOI: 10.1155/2017/9089068
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum IL-12p40 Is a Potential Predictor of Kasai Portoenterostomy Outcome in Infants with Biliary Atresia

Abstract: The standard-of-care treatment for biliary atresia (BA) is surgical restoration of bile flow by Kasai portoenterostomy. We aimed to study serum interleukin- (IL-) 12p40, a natural antagonist for the proinflammatory IL-12p70, and its relation to surgical outcomes of BA. The study included 75 infants with neonatal cholestasis: BA group (n = 25), non-BA cholestasis group (n = 30), and neglected BA group (n = 20), in addition to thirty healthy neonates serving as controls. IL-12p40 was measured by ELISA in all ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Specifically, IL-8 leads to bile duct injury, and decreased NLSR is associated with elevated circulating IL-8 levels at two months post Kasai [ 73 ]. Contrastingly, IL-12p40 or IL-12B, activate natural killer cells in proinflammatory cytokine IL-12p70, and this process is hypothesized to predict NLSR at Kasai [ 74 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, IL-8 leads to bile duct injury, and decreased NLSR is associated with elevated circulating IL-8 levels at two months post Kasai [ 73 ]. Contrastingly, IL-12p40 or IL-12B, activate natural killer cells in proinflammatory cytokine IL-12p70, and this process is hypothesized to predict NLSR at Kasai [ 74 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schneider et al, for example, suggested that failure to normalize serum bilirubin within three months after Kasai should elicit prompt evaluation for LT as extended native liver survival is exceptional among these patients [50]. Moreover, though a "Kasai success predicting score" remains far from reality, other groups support more research in that direction as part of BA management-a strategy that would allow early primary transplantation [47,54,[57][58][59][60][61].…”
Section: Steadily Increasing Prioritization Requestsmentioning
confidence: 99%